DETERMINAN KEPUTUSAN MENABUNG PADA NASABAH BANK MANDIRI (PERSERO) TBK DI KOTA KEDIRI - SILVIA DANI HAMID, AGUSTINA; ISBANAH, YUYUN (Jurnal Ilmu Manajemen (JIM), 2019)
This study aims to determine the influence of independent variables (understanding interest rates, understanding the inflation rates, level of knowledge, and location of bank) on the dependent variable (saving decision) on customers of Bank Mandiri (Persero) Tbk Kediri. This research is a causality study with simple random sampling. The data of this study is quantitative by collecting data by questionnaire. The data analysis technique used is multiple linear regression. The results of this study based on the t statistic test show that the level of knowledge and location of bank has a positive effect on saving decisions. Therefore, the variable understanding of interest rates and understanding the inflation rates avoid the saving decision. Based on the statistical test f, all independent variables simultaneously influence the dependent variable (saving decision). Keywords: inflation; interest; knowledge; location; saving.